Fertilizers for food and nutrition security in sub-Saharan Africa: An overview of soil health implications - Dimkpa, Christian; Adzawla, William; Pandey, Renu; Atakora, Williams K.; Kouame, Anselme K.; Jemo, Martin; Bindraban, Prem S. (Frontiers in Soil Science, 2023)
Sub-Saharan Africa (SSA) faces chronic food insecurity associated with soil degradation and the peculiar aftermath of climate change and exacerbated by rising population and historically poor agricultural practices. Notably, use of mineral fertilizers has the potential to counteract soil degradation in SSA; it drives an increased agricultural production required to feed the rising population while sustaining the quality and health of soils. However, limited financial resources deprive SSA of the promise of fertilizers, wherein application rates are historically low, and regimes are characterized by unbalanced nutrient composition and poor fertilizer quality. Although current global fertilizer use is generally characterized by low efficiency, SSA is most affected due to the already low usage and the quality of available fertilizer products. About 70% of fertilizer-nitrogen is lost through unregulated transformation to ammonia, nitrous oxide, and nitrate that are either volatilized or emitted into the atmosphere or leached into water bodies. Similarly, the preponderance of fertilizer-phosphorus is lost via run-off and leaching, unavailing it to plants while overloading streams and rivers and, together with nitrate, causing eutrophication. These environmental problems are accentuated in SSA where fertilizer quantity and quality issues are already a limiting factor. Notably, recent advances happening outside of SSA indicate that nutrients, when strategically formulated, such as by nano packaging, (bio)polymer encapsulation, and tunable to respond to environmental cues, can provide multiple outcomes, particularly, healthy soils with higher productivity. Therefore, presumably, a proper synthesis of the gamut of soil properties influencing plant nutrient release and availability, options for plant exposure and uptake is critical for realizing these benefits in SSA. Despite these possibilities, there is a lack of deeper context on fertilizer-related issues as they affect food and nutrition security and the health of soils in SSA. This paper provides an overview of the fertilizer-nutrient and associated agronomic, food insecurity and soil environmental challenges and opportunities, which though not exclusive to SSA per se, can be reasoned with the peculiarity of the region. This provides the impetus to increase fertilizer use efficiency, improve soil and environmental health, sustainable crop production, and food and nutrition security in SSA.